Pengaruh Dukungan Emosional terhadap Kepuasan Pernikahan Dewasa Awal di Provinsi Banten - Putri Rahayu Budiman; Santi Yudhistira; Herdiyan Maulana (Merpsy Journal, 2022)
This study aims to determine the influence of emotional support on early adult’s marital satisfaction in Banten Province. This study used quantitative method with the number of respondents as many as 170 early adults in Banten Province who are married. Data collection was carried out using an online questionnaire. The instruments used were the ENRICH Marital Satisfaction (EMS) Scale developed by Fowers and Olson (1993) to measure marital satisfaction and the Support in Intimate Relationships Rating Scale-Revised (SIRRS-Rating) developed by Barry et al. (2009) to measure emotional support. The analytical technique used is simple linear regression analysis with a parametric statistical approach. The results of this study indicate that there is an influence of emotional support on early adult’s marital satisfaction in Banten Province with a significance value of 0,000.